GE_GERICHTE P/8662/2012 vom 23. August 2018 - GE Cour de justice (2018)
ATTÉNUATION DE LA PEINE ; SURSIS À L'EXÉCUTION DE LA PEINE ; CONCOURS D'INFRACTIONS | CP.134; CP.123.ch1; CP.128.ch1; LCR.95.al1.leta; LCR.91a.al1; CP.140.ch1; LCR.90.al1